P-286 Can laser assisted hatching help implantation of warmed blastocysts in presence of fragmented cells ?. (30th June 2022) - Sanguinet, P; Regnier-Vigouroux, G; Keppi, B; Chiron, A; Montagut, M; Queré, G; Nogueira, D
Abstract: Study question: Does laser assisted hatching (LAH) following warming of blastocysts containing fragmentated cells improves blastocyst expansion and implantation? Summary answer: The application of LAH does not improve blastocyst expansion and implantation regardless the presence or absence of fragmented cells. What is known already: The absence of natural hatching is one of the hypotheses of implantation failure after cryopreservation, a process that could lead to hardening of the zona pellucida. Another theory is the fact that cellular fragments inside the zona pellucida, surrounding the trophectoderm, could impairs the exit of the blastocyst through the zona decreasing its chances of implantation. Available data regarding the effect of LAH on blastocysts after vitrification are inconclusive and limited to small samples. Evaluating the effectiveness of LHA performed at the time of blastocyst warming when cellular fragments are present could elucidate its impact on hatching and implantation Study design, size, duration: A bicentric prospective randomized study including 344 successive FET cycles from January 2020 until March 2021. Patients were enrolled only once in the study. Patients underwent a natural cycle or hormonal replacement treatment for FET. Blastocysts graded ≥ BL3BB (Gardner scoring) underwent artificial collapse and were vitrified on D5 or D6. Only blastocysts surviving post-warming were considered in the analysis. Primary end point was clinical pregnancy rate. Participants/materials, setting, methods: Patients ≤42 years with ≤3 previous oocyte retrievals scheduled for the first elective single embryo transfer (eSET) with vitrified/warmed blastocysts. Survived blastocysts were randomized immediately after warming to LAH group (n = 172) or to control group (no-LAH, n = 172). Cellular fragmentation was annotated as a percentage of the total volume of the embryo (0%, ≤25%, ≤50%, >50%) and LHA was performed on the opposite side. Embryo expansion was annotated at time of transfer, at 3 hours post-warming. Main results and the role of chance: Patients age were similar between LHA (33.1±9.3) and controls (34.8±7.5). Patients in LAH and controls had similar pregnancy rates (hCG >100) (46% versus 52%, respectively), CPR (37% versus 36%, respectively) (NS) and miscarriage rates. No difference was observed in CPR in relation to patients age. A significant increase in implantation was observed when blastocyst expansion took place 3 hours after warming, independently whether allocated in LAH (47% versus 17%, p < 0.01) or no-LAH group (51% versus 33%, p < 0.01). LAH did not influence cell expansion (83% in LAH versus 85% in no-LAH), however more blastocysts underwent hatching in LAH group (27% versus 12% in no-LAH, p < 0.06). Significantly more embryos that had hatched in LAH group led to pregnancy compared to no-LHA (83% versus 67%, respectively) (p = 0.05). Extra-cellular (EC) fragmentation not did not impact implantation in neither of the groups. LAH group had 46% of embryos implanted when absence of fragmentation, 40% when EC was present at ≤ 25%, 58% when EC was present at > 25% (NS). In no-LAH group, 52% of embryos implanted when absence of fragmentation, 49% when EC was present at ≤ 25%, 65% when EC was present at > 25% (NS). Limitations, reasons for caution: A sample size of 700 blastocysts was first chosen calculating a 10% difference in clinical pregnancy rate (CPR) between LAH-group and no-LAH group. The study was interrupted following this interim analysis. Live birth outcomes should be considered in a further analysis to conclude on the null impact of LHA post-warming. Wider implications of the findings: This study adds to the evidence of the existence of a limited potential of the application of LAH on vitrified-warmed blastocysts and its impact in terms of clinical pregnancy rates. Trial registration number: not applicable